Informatyzacja gospodarki opartej na wiedzy (GOW) - Biernat, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Mechanisation, automation, using robots in production processes; making use of computers, virtual processes, fractal processes of enterprises' activity; integration process (mergers alliances) of organization systems (globalisation); political, economy-wise and geographical integration (European Union) - they shape the new basics of the way organizations function (those based on knowledge, learning organizations and intelligent ones). They also shape society relations (knowledge management, social capital, intellectual capital, capital of relations), creating the entity of individuals, leaders, groups, local communities. Scientific diagnosis resulting from the applied research method (analysis of work/labour synthesis, knowledge synthesis) points out the subsequent phases of the development of civilization: post-industrial society, information society and - in future - in the society of knowledge, in with the knowledge is the basis for labour valuation and for social divisions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 39-49